Épocas relativas de plantio nos consórcios mamona/amendoim e mamona/gergelim em condições de sequeiro - Araújo Filho, José Otávio Targino de (2005)
The castor bean presents, with its physiology, morphology and phenology, the opportunity to produce accompanied by other crops, such as legumes. However, care must be taken that there is no high level of competition, whether by light, nutrients, water or carbon dioxide. With the need to maximize the production of oil in the same area there is the possibility of producing castor bean in consortium with other oil seeds, such as peanuts and sesame. The objective of this work was to define the best time to cultivate the planting of the castor bean crop, minimizing the effect of competition. The experiments were carried out in the city of Areia - PB, using castor bean cultivar BRS 149 - Nordestina, at a spacing of 3.0 x 1.0 m, one plant per pit, intercropped with peanut, BR 1 and sesame cultivate G4, spaced 0.5 x 0.2 m. The treatments were: control (M1 and M2), (G1 and G2) and (A1 and A2) and planted on the same day; culture consort planted 7 days after castor bean, culture consort planted 15 days after castor bean; and culture consort planted 22 days after castor bean. The statistical design was in randomized blocks and the variables studied were: plant height (ATL), stem diameter (DIAM), number of leaves (NF), number of bunches (NC), height of first bunch ), number of bunches per plant (NCP) and number of fruits per cluster (NF). The studied variables of the peanut were healthy seeds (SS), seeds (SC), initial stand (EI), final stand (EF), fruit weight with peel (CCP), seed weight NF). The variables studied for sesame were height of plants (AP), height of the first fruit (FA) m, initial stand (EI), final stand (EF), number of fruits (NF), number of branches (NR). And for the three cultures a thousand seeds weight (PMS),% oil and productivity (PD). For the consortium system the use of land efficiency (UET) and monetary advantage (VM) was calculated. The morphological (ALT, DIAM, NF) and productive (NC and PD) data were negatively influenced by the smaller planting intervals of peanut intercropped by castor bean. Longer time intervals are recommended to reduce competition and single castor cashew produces more than the intercropper. The best season for the castor bean / sesame consortium occurred at 22 days of castor bean cultivation and the productive characteristics were adversely affected by the consortium; the vegetative ones behaved regardless of the form of management used.